2013
DOI: 10.1519/jsc.0b013e318279423e
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sprinting Activities of Professional Soccer Players

Abstract: The aim of the study was a detailed analysis of the sprinting activity of professional soccer players. The study involved 147 players who played in 10 matches of the 2008-09 and 2010-11 UEFA Europa League seasons. The number of performed sprints and total sprint distances covered by the players were examined using collected statistical material. Two types of sprints were distinguished based on their duration: S, short-duration sprint (below 5 seconds) and L, long-duration sprint (above 5 seconds). Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 30 publications
5
75
0
11
Order By: Relevance
“…For professional players, Andrzejewski et al (2013) reported that 90% of sprints were performed within 5 seconds. Some authors consider the player’s first steps and the ability to gradually increase their speed as the most important component of the running performance during the game (Dellal et al, 2011; Sleivert and Taingahue, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For professional players, Andrzejewski et al (2013) reported that 90% of sprints were performed within 5 seconds. Some authors consider the player’s first steps and the ability to gradually increase their speed as the most important component of the running performance during the game (Dellal et al, 2011; Sleivert and Taingahue, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Less time was spent walking, more time was spent jogging and running, greater distance covered was covered LSR, and there was a higher TD and average speed during the 8-player drill (Table 1). A high level of fast running and sprinting was also completed in the 8-player SST drill (Table 2), over distances (approximately 10-20 m) specific to the sport (Andrzejewski et al, 2013, Greig et al, 2006, Spencer et al, 2005. This workload was reflected in the physiological data; the 8-player SST drill elicited a greater HR response than the 10-and 12-player drills (Table 3), and these data were comparable to HR responses of a similar sized SSG.…”
Section: Discussionmentioning
confidence: 86%
“…This further emphasises how the 8-player SST drill could be used to enhance aerobic fitness for soccer. In contrast, the sprints performed within the 10-and 12-player SST drills tended to be shorter, which is more reflective of sprints performed during a soccer match (Andrzejewski et al, 2013). This in turn highlights the specificity of these two drills in potentially targeting RSA and acceleration for soccer.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Podľa zistení Psottu et al (2006) je v samotnej futbalovej hre 50-65 % všetkých realizovaných šprintov kratších ako 5 m, 75-85 % všetkých šprintov nie je dlhších ako 10 m a priemerná dĺžka šprintov je 9 m. Grasgruber & Cacek (2008) uvádzajú dĺžku šprintov cca 15 m a spravidla nie viac ako 30 m, každých cca 90 s, čo vychádza za celý zápas 0,8 až 1 km. Andrzejewski et al (2012) zistili u profesionálnych hráčov európskych líg, že 90 % všetkých realizovaných šprintov v zápasoch je do 5 sekúnd. Podľa výskumov dosahujú profesionálni hráči významne vyššiu rýchlosť v prvých 10 m šprintov pri porovnaní s hráčmi nižších súťaží (Grasgruber & Cacek, 2008, Psotta et al, 2006.…”
Section: úVodunclassified